Numerical Simulation of the effect of L-shaped spur dike wing length on scouring at a 90 ° bend. - Mousa Rasaei (Journal of Hydraulic Structures, 2022)
Spur dike is one of the common structures in organizing and controlling erosion on the river bank. On the other hand, the placement of the spur dike in the bended part of the river, while removing strong currents from the shore and directing the flow to the river axis, also changes the flow pattern and scour around the spur dike. The aim of this study was to numerically investigate the effect of length change in L-shaped Spur dike wing on scour depth located in a channel with a 90° bend. For this purpose, the three-dimensional SSIIM numerical model was used for simulation. L-shaped spur dikes with different wing lengths were tested and simulated. At the end, the outputs of the numerical model were compared with the laboratory results and validated. The results while confirming the SSIIM numerical model in scour simulation around the spur dike showed that by increasing the length of the spur dike wing and decreasing the angle of the spur dike in the bend, the depth and volume of the scour decreases significantly. In addition, the maximum depth and volume of scour around the spur dike was recorded at a 90 ° angle with a length to web ratio of 0.5. On the other hand, in all cases, scour around the simple spur dike was more than the L-shaped spur dike with different wing lengths.